Guilt, blame, litigation and training. (March 2017) - Marsh, Michael
Abstract : Deputy Editor‐in‐Chief, Dr Michael Marsh, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/march-editors-choice-2017 .